Mechanisms and Procedures for Teacher Protection at the Laboratory Schools of Universitas Pendidikan Indonesia - Ridwan Purnama; Asep Ridwan Lubis; Nabil Fatya NH (Indonesian Journal of Community Empowerment (IJCE), 2026)
This study aims to provide an understanding of teacher protection regulations and implement legal protection mechanisms at SMA Laboratorium UPI. The methods employed include lectures, discussions, and legal case studies involving teachers as the primary participants. The results indicate an increased understanding among teachers regarding their constitutional rights, professional protection, occupational safety, and Intellectual Property Rights (IPR). The study identified obstacles such as a lack of regulatory knowledge and limited access to legal aid in specific areas. It is concluded that synergy between the school institution, the community, and the government is essential to guarantee legal certainty and comprehensive protection for teachers in carrying out their professional duties.